2016
DOI: 10.1111/ajo.12439
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous birth outcomes at a Victorian urban hospital, a retrospective 5-year cohort study 2010-2014

Abstract: Heterogeneity of indigenous people and geography means that inferences about indigenous health are difficult to make. It appears that Victorian urban indigenous women have similar rates of preterm birth and LBW to nonindigenous women. While there were pleasing results concerning LBW, antenatal care, diabetes and preterm birth, the rates of smoking and obesity remain a challenge in the indigenous population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…A similar retrospective cohort study was recently conducted in a non-tertiary Melbourne hospital, which concluded similar rates of low birthweight to Aboriginal and non-Aboriginal parents [ 25 ]. This discrepancy may firstly be due to differences in defining Aboriginal status, where maternal and paternal Aboriginal status was recorded on one database and the ethnicity of the baby was allocated if either parent was Aboriginal.…”
Section: Discussionmentioning
confidence: 85%
“…A similar retrospective cohort study was recently conducted in a non-tertiary Melbourne hospital, which concluded similar rates of low birthweight to Aboriginal and non-Aboriginal parents [ 25 ]. This discrepancy may firstly be due to differences in defining Aboriginal status, where maternal and paternal Aboriginal status was recorded on one database and the ethnicity of the baby was allocated if either parent was Aboriginal.…”
Section: Discussionmentioning
confidence: 85%
“…Indigenous women bear a higher burden of diabetes in pregnancy in Australia and elsewhere . About 4% of Australians identify as indigenous, varying from region to region: around 1% in Victoria, more than one in four in the Northern Territory and more than one in two in the Cape York region of Far North Queensland . Rural‐remote compared with urban domicile appears to confer additional health risks for Aboriginal infants born to mothers with diabetes in pregnancy …”
Section: Resultsmentioning
confidence: 99%
“…First Nations pregnant women face a double burden of malnutrition, with both macronutrient undernutrition and overnutrition detected more commonly when compared to non‐Indigenous women 19,52‐54 52 .…”
Section: Risk Factors For Ptb In First Nations Womenmentioning
confidence: 99%